Addressing Challenges in Palladium‐Catalyzed Cross‐Couplings of Aryl Mesylates: Monoarylation of Ketones and Primary Alkyl Amines1. Issue 28 (12th June 2013) - Alsabeh, Pamela G.; Stradiotto, Mark
<x xml:space="preserve">Abstract</x> Mor(DalPhos) for Me(sylates): Described are the first examples of ketone mono‐α‐arylation and primary aliphatic amine monoarylation employing aryl methanesulfonate coupling partners. A range of functionalized aryl mesylates were employed with dialkyl ketones, and also with primary and secondary amines as well as the otherwise challenging coupling partners acetone and methylamine. Ad=adamantyl.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>